J Nanotechnol Nanomaterials 2020
DOI: 10.33696/nanotechnol.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanotechnology: The Influence of Intermolecular and Supramolecular Interactions

Abstract: Green nanotechnology seeks eco-friendly solutions, capable of generating efficient nanotechnological protocols with low or no environmental impact. These nanosystems are marked out by intermolecular and supramolecular interactions capable of stabilizing the nanostructures and making nanotechnology effective. Many synthesis methodologies are being developed that involve a variety of biological sources. Among them, it can highlight biosynthesis using plant extracts. They are simple, cheap syntheses and have a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Another essential factor to be considered is that more eco-friendly conditions of pH, temperature, and pressure are adopted during green synthesis and the establishment of protocols with reactions that generate few or no by-products. Thus, the synthesis needs to be sustainable throughout the process including the disposal [ 29 , 30 , 31 , 32 ].…”
Section: Synthesis Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another essential factor to be considered is that more eco-friendly conditions of pH, temperature, and pressure are adopted during green synthesis and the establishment of protocols with reactions that generate few or no by-products. Thus, the synthesis needs to be sustainable throughout the process including the disposal [ 29 , 30 , 31 , 32 ].…”
Section: Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…As a result, an important reduction of waste, cost, and environmental impact. It has also been reported that green synthesis using vegetable extracts or oils tends to be simple and fast, requiring fewer steps and hence minimizing the possibility of exposure [ 31 ]. Safety and control measures also need to be taken during handling to prevent accidental NM emissions.…”
Section: Challengesmentioning
confidence: 99%